Principles of medicine in Africa - Weber, Martin W. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2025)
"This book is for medical officers working in Africa. It provides up to date, practical information on the pathogenesis, clinical features, diagnosis, treatment and prevention of all the diseases they are likely to encounter in an easily accessible format"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Tropical Medicine -- methods; Public Health Practice; Africa